2002
DOI: 10.1093/glycob/12.4.273
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a new  -L-fucosidase isolated from the marine mollusk Pecten maximus that catalyzes the hydrolysis of  -L-fucose from algal fucoidan (Ascophyllum nodosum)

Abstract: Algal fucoidan is an alpha-L-fucose-based polysaccharide endowed with important biological properties for which the structure has not yet been fully elucidated. In an attempt to implement new enzymatic tools for structural study of this polysaccharide, we have found a fucosidase activity in the digestive glands of the common marine mollusk Pecten maximus, which is active on a fucoidan extracted from the brown algae Ascophyllum nodosum. We now report the purification and characterization of this alpha-L-fucosid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
61
1
6

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 34 publications
1
61
1
6
Order By: Relevance
“…5b). Despite different oligomeric states being reported for many prokaryotic and eukaryotic GH29 enzymes (16,20,23,24, 27, 36), we did not find any evidence for oligomerization.…”
Section: Resultscontrasting
confidence: 87%
See 1 more Smart Citation
“…5b). Despite different oligomeric states being reported for many prokaryotic and eukaryotic GH29 enzymes (16,20,23,24, 27, 36), we did not find any evidence for oligomerization.…”
Section: Resultscontrasting
confidence: 87%
“…Depending on the specificity of ␣-L-fucosidases, they actively hydrolyze a variety of terminal fucosyl linkages typically in the form of ␣1,2 linkages to D-galactose (Gal), ␣1,3/4/6 linkages to N-acetylglucosamine (GlcNAc), ␣1,3 linkages to D-glucose (Glc) that are present in different natural substrates like milk oligosaccharides, plant cell wall polysaccharides, various glycoproteins, or glycolipids harboring various A, B, H, and Lewis blood group antigens or their analogs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24). In addition, ␣-L-fucosidase isolated from the marine mollusk Pecten maximus has been reported to efficiently release fucose without extensive depolymerization of fucoidan from Ascophyllum nodosum (24), which contains alternating Fuc␣1-4Fuc and Fuc␣1-3Fuc backbone units (14). On the other hand, an exofucosidase from abalone (Haliotis gigantea) liver has been demonstrated to catalyze complete hydrolysis of fucoidan from brown alga Ecklonia cava (25).…”
mentioning
confidence: 99%
“…1 ␣-L-Fucosidases have been shown to follow a double displacement mechanism with net retention of the anomeric configuration, as initially proposed for human liver ␣-L-fucosidase in 1987 (18) and recently confirmed by biochemical studies on ␣-L-fucosidases from Thermus sp. Y5 (19), the marine mollusc Pecten maximus (20), Sulfolobus solfataricus (21), and Thermotoga maritima (22).…”
mentioning
confidence: 99%
“…Recent work has demonstrated that ␣-L-fucosidases are retaining enzymes; the hydrolyzed hemiacetal product bears the same stereochemical configuration as the original glycoside (11,12). In the vast majority of these cases this stereochemical outcome arises from a double displacement mechanism within the enzyme active site.…”
mentioning
confidence: 99%